2014
DOI: 10.1097/igc.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Feasibility of Robotic-Assisted Lymph Node Staging in Early-Stage Ovarian Cancer

Abstract: The results from this study suggest that robotic-assisted surgical staging in the management of presumed early-stage ovarian cancer is both feasible and associated with a minimal patient complication rate. We encountered a low incidence of lymph node metastases, and the readmission rate was favorable. Nevertheless, because the prevalence of lymph node metastases can approach 20% in select patients, physicians should consider a systematic lymph node resection to confer an optimal clinical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Hence, patients with advanced ovarian cancer requiring extensive debulking may be best approached by laparotomy. Recently, other authors have reported similar lymph node yields and survival with the robot-assisted approach compared with laparotomy (5,42). In 2014 Nezhat et al compared 47 cytoreductive procedures in stages II-IV and recurrent cancer and found similar maximal cytoreduction and complication rates in robot-assisted, laparoscopy, and laparotomy (43).…”
Section: Ovarian Cancermentioning
confidence: 96%
“…Hence, patients with advanced ovarian cancer requiring extensive debulking may be best approached by laparotomy. Recently, other authors have reported similar lymph node yields and survival with the robot-assisted approach compared with laparotomy (5,42). In 2014 Nezhat et al compared 47 cytoreductive procedures in stages II-IV and recurrent cancer and found similar maximal cytoreduction and complication rates in robot-assisted, laparoscopy, and laparotomy (43).…”
Section: Ovarian Cancermentioning
confidence: 96%
“…2 For advanced ovarian cancer, PALND is usually performed as part of open surgery, but for clinically early-stage cancer or secondary staging, the robotic-assisted technique is a better alternative providing faster recovery. 6,7 On the other hand, minimally invasive surgery is the treatment of choice for the majority of patients with endometrial cancer, either using traditional or robotic-assisted technique. Although in general no significant differences in the number of pelvic and para-aortic nodes harvested using either technique have been found, 8 especially in obese women PALND is challenging to perform using the traditional approach, and the number of conversions has been lower in robotic-assisted surgery than in traditional laparoscopic surgery.…”
mentioning
confidence: 99%
“…Removal of the infrarenal aortic nodes, in particular the left group, can be challenging due to the presence of large vessels, frequent anatomical vessel anomalies of this area, close proximity of the camera port and narrow operative field . Data describing robot‐assisted staging of early‐stage ovarian cancers is limited (Table ) . Nezhat et al .…”
Section: Resultsmentioning
confidence: 99%
“…Brown et al . presented their experience with staging 26 stage Ia–IIc ovarian carcinoma patients. Their EBL, operating times (OT), and number of lymph nodes were comparable to previously reported laparoscopic staging procedures in early‐stage ovarian cancers.…”
Section: Resultsmentioning
confidence: 99%